Evaluation of a clinical medical librarianship program at a university Health Sciences Library. - Schnall, J G (1976)
An evaluation of the clinical medical librarianship program at the University of Washington Health Sciences Library was undertaken to determine the benefits of the program to patient care and to the education of the recipients of the service. Results of a questionnaire reflected overwhelming acceptance of the clinical medical librarianship program. Guidelines for the establishment of a limited clinical medical librarianship program are described. A statistical cost analysis of the program is included.